2013
DOI: 10.4028/www.scientific.net/amr.747.522
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Reinforced Natural Rubber with Epoxidized Low Molecular Weight Rubber as a Compatibilizer

Abstract: This work investigates the effect of epoxidized low molecular weight natural rubber (ELMWNR) in silica-filled NR compounds on processing, mechanical and dynamic mechanical properties. The ELMWNRs with mol% epoxide groups varying from 0-50 and molecular weight in a range of 50,000-60,000 g/mol were prepared from depolymerization of epoxidized natural rubber using periodic acid in latex state. They were then added in the silica-filled NR compounds as a compatibilizer at varying loading from 0-15 phr. The additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The reinforcement index was calculated by dividing the modulus at 300% elongation by the modulus at 100% elongation. It is used to assess rubber–filler interactions . It was found that the reinforcement index of NR/silica composites significantly increased with grafting level in NR‐g‐PHEA, corroborating stronger rubber–silica interactions seen also in the bound rubber content in Figure , and causing a higher resistance to deformation.…”
Section: Resultsmentioning
confidence: 79%
“…The reinforcement index was calculated by dividing the modulus at 300% elongation by the modulus at 100% elongation. It is used to assess rubber–filler interactions . It was found that the reinforcement index of NR/silica composites significantly increased with grafting level in NR‐g‐PHEA, corroborating stronger rubber–silica interactions seen also in the bound rubber content in Figure , and causing a higher resistance to deformation.…”
Section: Resultsmentioning
confidence: 79%
“…Another more environmental friendly alternative is epoxidized natural rubber (ENR) which has been used both as compatibilizer [4] and as matrix [5] for silica-filled rubber compounds. Epoxidized low molecular weight natural rubber (ELMWNR) has been used as a compatibilizer to enhance processing and mechanical properties of silica-filled NR [6], but the properties are still inferior compared to the TESPT/silica system. As TESPT also plays a role as sulfur donor during mixing and vulcanization, and positively affects on the properties of silica/silane-filled NR [1], this present work investigates an influenece of extra sulfur added to the silica-filled NR compounds which are compatibilized with ELMWNRs.…”
Section: Introductionmentioning
confidence: 99%